PEMBELAJARAN PAI DENGAN MENGGUNAKAN MEDIA GOOGLE CLASSROOM PADA MASA PANDEMI DI SMPN 2 KOTA SOLOK - Juliwansyah, Juliwansyah; Sesmiarni, Zulfani (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2022)
Since the prolonged pandemic period which resulted in students who were initially accustomed to time discipline to study regularly, inevitably had to change because there was a government policy that explained that learning was done online. This research is a qualitative research, namely research in the form of a description that aims to understand the phenomena that occur in research subjects. The results of the study show that the implementation of PAI learning in class X SMPN 2 Kota Solok during the pandemic season is by using Google Classroom media. The stages taken include; planning, implementing, organizing, and evaluating learning. The supporting factors for learning are; Google Classroom learning media workshops for teachers and students, strong network and internet, students have smartphones, and enthusiastic parents. While the inhibiting factors of learning are; there is a bad internet network due to natural conditions, resulting in easily distracted student concentration, and less than optimal application of blended learning.